Managing attention deficit hyperactivity disorder in adults using illicit psychostimulants: A systematic review. (September 2017) - Cook, Jon; Lloyd-Jones, Martyn; Arunogiri, Shalini; Ogden, Edward; Bonomo, Yvonne
Context: Attention deficit hyperactivity disorder and stimulant use disorder commonly co-exist, and appropriate treatments have not been well established. Objective: To provide guidance for treatment of co-existing attention deficit hyperactivity disorder and stimulant use disorder. Data sources: A systematic review of published English articles using MEDLINE, EMBASE, CINAHL, PsycINFO and Cochrane, utilising consistent search terms. Study selection: Randomised controlled trials, comparing any treatment arm with a control group, for participants meeting Diagnostic and Statistical Manual of Mental Disorders or equivalent criteria for both attention deficit hyperactivity disorder and stimulant use disorder. Results: Eight trials were identified for inclusion in this review. Four of eight studies showed improvement in attention deficit hyperactivity disorder outcome measures compared with placebo. Two of six studies that reported substance use outcomes showed improvement in treatment arms compared with placebo. Studies to show effect tended to be those with the highest treatment dosage. Conclusion: Evidence for the efficacy of treatment of patients with comorbid stimulant use disorder and attention deficit hyperactivity disorder is limited. Promising outcomes need replication in further studies utilising higher treatment dosage.